Analysis of Factors Affecting Out-of-School Children (OOSC) in Pasuruan Regency: Analisis Faktor-Faktor yang Mempengaruhi Anak Tidak Sekolah di Kabupaten Pasuruan - Zhenira Farellina Azka Zeta Zeta (Universitas Bojonegoro, 2026)
This study aims to analyze the influence of the percentage of the poor population and the number of schools on the percentage of out-of-school children (OOS) in Pasuruan Regency in 2025. This study employs a quantitative approach using multiple linear regression analysis with robust standard errors. The research data consists of secondary data from 24 subdistricts in Pasuruan Regency, which was analyzed using the Stata software. The results indicate that the percentage of the poor population has a positive and significant effect on the percentage of Out-of-School Children (OOS), whereas the number of schools does not have a significant effect on the OOS percentage. An R-squared value of 0.771 indicates that the variables of the percentage of the poor population and the number of schools account for 77.1% of the variation in OOS. This study indicates that economic factors remain a key factor influencing the high percentage of ATS in Pasuruan Regency.